A comparison of viral microneutralization and haemagglutination inhibition assays as measures of seasonal inactivated influenza vaccine immunogenicity in the first year after reduced intensity conditioning, lymphocyte depleted allogeneic haematopoietic stem cell transplant. Issue 3 (14th January 2019) - Miller, Paul D.E; de Silva, Thushan I.; Leonard, Hayley; Anthias, Chloe; Hoschler, Katja; Goddard, Kathryn; Peggs, Karl; Madrigal, Alejandro; Snowden, John A.
Abstract: Traditionally, immune response to influenza vaccines has been measured using the haemagglutination inhibition (HAI) assay. A broader repertoire of techniques including the sensitive viral microneutralization (VMN) assay is now recommended by the European Medicines Agency (EMA). Comparing HAI and VMN, we determined immune response to a trivalent 2015–2016 seasonal inactivated influenza vaccine (SIIV) administered to 28 recipients of allogeneic haematopoietic stem cell transplant (HSCT). Vaccination was within the first-year post-transplant at a median of 78.5 (24–363) days. The proportion of patients with baseline and post-vaccination HAI titres ≥ 1:40 were 28.6% and 25% for A(H1N1)pdm09, 14.3% at both timepoints for A(H3N2), and 32.1% and 25% for B(Phuket). Pre and Post-vaccination geometric mean titres(GMT) were higher by VMN than HAI for A(H1N1)pdm09 and A(H3N2), but lower for B(Phuket)(p=<0.05). Geometric mean ratios(GMR) of baseline and post-vaccination titres were similar by HAI and VMN(p > 0.05) for all components. A single seroconversion to A(H1N1) was detected by ELISA-VMN. None of patient age, lymphocyte count, days from transplant to vaccination, donor type, or graft-versus-host disease (GVHD) or immunosuppressive therapy (IST) at vaccination correlated with baseline or post-vaccination titres by either assay. This absence of seroresponse to SIIV in the first-year post HSCT highlights the need for novel immunogenic vaccination formulations and schedules in this high-risk population.